2000
DOI: 10.1111/1467-6486.00221
|View full text |Cite
|
Sign up to set email alerts
|

Porter’s Competitive Advantage Of Nations: Time For The Final Judgement?

Abstract: Porter’s (1990) Competitive Advantage of Nations (CAN) was heralded on publication as a book which could build a bridge between the theoretical literatures in strategic management and international economics, and provide the basis for improved national policies on ‘competitiveness’. This review of CAN draws on papers written since its publication to show that while it was enormously rich in its range and scope it fell far short of the claims made for it. That failure arose from a number of sources. Most fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 37 publications
1
93
0
4
Order By: Relevance
“…Davies & Ellis, 2000). This finding adds to other studies that have found that firm success within a country may be driven by demand conditions in trading partners' countries (Espana, 2004;Rugman & D'Cruz, 1993;Rugman & Verbeke, 1993a, 1993b.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Davies & Ellis, 2000). This finding adds to other studies that have found that firm success within a country may be driven by demand conditions in trading partners' countries (Espana, 2004;Rugman & D'Cruz, 1993;Rugman & Verbeke, 1993a, 1993b.…”
Section: Discussionsupporting
confidence: 65%
“…While Porter's model is now included in most standard texts in strategy and international business (e.g., Grant, 2001;Hill & Jones, 2004;Hodgetts, Luthans & Doh, 2005), and has been widely utilized in practice, it has been subject to substantial criticism at various levels (see Bellak & Weiss, 1993;Cartwright, 1993;Davies & Ellis, 2000;Dunning, 1993;Grant, 1991;Grein & Craig, 1996;Rugman, 1991;Rugman & Verbeke, 1993a, 1993b. 3 At a conceptual level, several scholars have critiqued the fundamental assumptions and assertions of the model.…”
Section: The Diamond Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while recent empirical studies have shed new light on the structure and dynamics of cluster-like phenomena in particular industry sectors and geographic locations (Lorenzen 1998, Requier-Desjardins et al 2003, van Dijk and Sverrisson 2003), there has also been an increasingly polarized debate regarding the way in which the core concept has been developed and applied. Critics argue that proliferation of the clusters literature has brought with it a confusing variety of definitions, and a general lack of clarity over some of the key definitional parameters such as the drawing of spatial and sectoral boundaries.2 The 'diamond' framework had attracted particularly strong criticism, with detractors arguing that its conceptual limitations are a hindrance to empirical research, with potentially damaging effects on regional policies (Davies and Ellis 2000, Simmie 2002, Palazuelos 2005. More specifically, the framework is seen as conflating processes that operate at different spatial scales, and compressing the complex temporality of causal relationships:…”
Section: Globalization Pressures and The 'Clusters' Debatementioning
confidence: 99%
“…The focus of the empirical study is on explaining differences in cluster dynamics; this allows us to assess the capacity of each conceptual framework to probe causal relationships over time and across multiple levels of analysis (cf. Davies and Ellis 2000: 1205-1206). …”
Section: Globalization Pressures and The 'Clusters' Debatementioning
confidence: 99%